Effect of different water regime on microorganisms of nitrogen cycle in permafrost - Turková, Sára (Jihočeská univerzita, 2022)
The gene abundances and community structures of nitrogen-fixing and denitrifying bacteria in permafrost-affected soils with different moisture level were analysed. Additionally, DNA- and RNA-based analysis was used to evaluate the variations in gene copy numbers and community composition between the total and active bacteria. The gene abundances of nitrogen-fixing and denitrifying bacteria were quantified by qPCR of the nifH and nosZ genes, and the gene copy numbers were compared between the soils with different moisture. Furthermore, the bacterial community structure variation was evaluated by analysis of the taxonomic classification obtained from sequencing data.
Effect of different water regime on microorganisms of nitrogen cycle in permafrost
Keywords: Arctic; permafrost thaw; soil moisture; nitrogen cycle; nifH; nosZ; gene abundance; qPCR; bacterial community structure; Arctic; permafrost thaw; soil moisture; nitrogen cycle; nifH; nosZ; gene abundance; qPCR; bacterial community structure